Milk Proteins : From Structure to Biological Properties and Health Aspects - Gigli, Isabel; Gigli, Isabel (IntechOpen, 2016)
Milk proteins have nutritional value and extraordinary biological properties. Research over the last decades has provided new insight into the structure and the function of milk bioactive peptides. Some of these peptides are delivered directly into milk, and some are encrypted in major proteins such as caseins and lactoglobulins. These peptides have antimicrobial functions modulating the gut microflora. Even when milk is undisputedly the first food for mammals, milk proteins sometimes can be a health threat, either because of allergic reaction or because of toxicity. In this regard, in vitro studies showed donkey's casein and major whey proteins to be more digestible than cows' for human consumption. In this book, readers will find updated research on the major milk proteins' structure, bioactive peptides, milk protein allergy, therapeutic strategies, and chemical markers that can be used to detect cow milk intolerance in infants. This book provides the most current scientific information on milk proteins, from structure to biological properties. It will be of great benefit for those interested in milk production, milk chemistry, and human health.
English
Keywords: Biochemistry; Biochemistry